Haemothorax in a Pregnant Woman Secondary to Rupture of a Pulmonary Arteriovenous Malformation - Melissa van den Bulck; Claude Berenger Ngah; Hyppolyte Ntula; Yilmaz Gorur; Benoît Cardos; Denis Brisbois; Noel Lorenzo Villalba; Deeba Ali (European Journal of Case Reports in Internal Medicine, 2022)
Pulmonary arteriovenous malformations (PAVMs) are abnormal communications between the arteries and veins of the pulmonary vasculature leading to a right-to-left shunt. We report the case of a pregnant patient who presented with chest pain revealing a haemothorax secondary to the rupture of an arteriovenous malformation. The diagnosis was made during arteriography after simultaneous performance of an urgent caesarean section and thoracic drainage.